2014
DOI: 10.1155/2014/641039
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Triggering Receptor Expressed on Myeloid Cells-1 and Procalcitonin Can Reflect Sepsis Severity and Predict Prognosis: A Prospective Cohort Study

Abstract: Objective. To investigate the prognostic significance of serum soluble triggering receptor expressed on myeloid cells-1 (sTREM-1), procalcitonin (PCT), N-terminal probrain natriuretic peptide (NT-pro-BNP), C-reactive protein (CRP), cytokines, and clinical severity scores in patients with sepsis. Methods. A total of 102 patients with sepsis were divided into survival group (n = 60) and nonsurvival group (n = 42) based on 28-day mortality. Serum levels of biomarkers and cytokines were measured on days 1, 3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
5
37
0
2
Order By: Relevance
“…Five cytokines, RANTES, EGF, VEGF R3, MIP-1δ, and LAP, showed significant and consistent differences between the two groups and were selected for further analysis. Changes in the MCP-1 and IL-6 expression levels were opposite but obviously different between the two groups, consistent with previous reports (Mera et al 2011;Li et al 2014), which demonstrated the value of MCP-1 and IL-6 levels in predicting mortality for patients with sepsis. Therefore, we researched these two cytokines, in addition to the five cytokines mentioned above.…”
Section: Screening Of Plasma Samplessupporting
confidence: 92%
“…Five cytokines, RANTES, EGF, VEGF R3, MIP-1δ, and LAP, showed significant and consistent differences between the two groups and were selected for further analysis. Changes in the MCP-1 and IL-6 expression levels were opposite but obviously different between the two groups, consistent with previous reports (Mera et al 2011;Li et al 2014), which demonstrated the value of MCP-1 and IL-6 levels in predicting mortality for patients with sepsis. Therefore, we researched these two cytokines, in addition to the five cytokines mentioned above.…”
Section: Screening Of Plasma Samplessupporting
confidence: 92%
“…Especially appealing was the assessment of sTREM-1, because it was the only molecule significantly correlated with both the SOFA and APACHE II scores. This is a previously demonstrated finding; effectively, serum sTREM-1 levels are significantly different in patients with sepsis compared to those with severe sepsis/septic shock [3537] and these levels were correlated with the SOFA score [38]. Moreover, a correlation between sepsis severity and serum levels of IL-6 [39] and PCT [23,37,4042] had been observed previously.…”
Section: Discussionsupporting
confidence: 78%
“…(27,28,30,31,32) These studies indicate that serial PCT measurements are considered a possible marker of prognosis.…”
Section: Introductionmentioning
confidence: 94%